Optimalisasi Pemanfaatan Limbah Pertanian: Menciptakan Produk Keripik Bernilai Ekonomis dari Kulit Pisang Raja Nangka di Kabupaten Jombang - Pamungkas, Kevin Dyo; Raharjo, Djoko; Supandji; Tafakresnanto, Chendy (Kadiri University, 2025)
The utilization of agricultural waste presents a crucial challenge in the context of sustainable development, particularly in promoting effective waste management systems and environmental preservation. Raja Nangka banana peel, a common by-product discarded in high volumes by MSMEs in Jombang Regency, is known to possess significant nutritional and fiber content that can be utilized. This community engagement program aims to address this waste problem by transforming banana peels into high-value food chips. The program focused on Micro and Small Enterprise (MSMEs) groups in Jombang Regency, involving 5 main participants. The methodology employed a technology transfer approach through intensive training, direct practice demonstration, and evaluation based on observing the active participation of the MSME partners. The process included optimization of the formula (limewater soaking), efficient production, and subsequent analysis of proximate content and Hayami Value Added. The results demonstrated that the innovative chip product possessed good food quality, featuring high Carbohydrate content (71.54%) and sufficient Protein (6.30%). From an economic standpoint, the Cost of Goods Sold (COGS) proved to be very efficient (IDR3,245 per unit), yielding a total value added of IDR24,225 per kilogram and resulting in a substantial value added Ratio (96.9%). This success confirms that the intervention is feasible for replication, offering a measurable solution to minimize solid waste in the agricultural sector while simultaneously enhancing capacity, proving autonomous technology adoption, and ensuring the economic sustainability of the local community. Pemanfaatan limbah pertanian saat ini menjadi isu krusial dalam konteks pembangunan berkelanjutan terutama dalam mendorong sistem pengelolaan lingkungan yang lebih efektif. Kulit pisang Raja Nangka sebagai merupakan produk sampingan yang dihasilkan oleh industri UMKM dalam volume tinggi di Kabupaten Jombang. Kulit pisang tersebut diketahui memiliki kandungan nutrisi dan serat yang dapat diolah dan dimanfaatkan. Kegiatan pengabdian masyarakat ini dilakukan untuk mengatasi masalah limbah tersebut dengan mentransformasi kulit pisang menjadi keripik bernilai jual tinggi. Dengan fokus peserta adalah kelompok usaha kecil dan mikro (UMKM) di Kabupaten Jombang yang melibatkan 5 orang peserta utama. Metodologi pengabdian ini dilakukan menggunakan pendekatan transfer teknologi melalui pelatihan intensif, demonstrasi praktik langsung, dan evaluasi berbasis observasi partisipasi aktif mitra UMKM. Proses kegiatan mencakup optimasi formulasi dengan perendaman larutan kapur, produksi yang efisien, dan uji analisis proksimat serta analisis nilai tambah Hayami. Hasil pengabdian inovasi produk ini menunjukkan produk keripik memiliki mutu pangan yang baik dengan kandungan karbohidrat 71,54% dan protein 6,30%. Dari segi aspek ekonomi analisis menunjukkan HPP yang sangat efisien (Rp 3.245 per unit) dan perolehan dari analisis nilai tambah sebesar Rp 24.225 per kg, menghasilkan rasio nilai tambah yang substansial (96,9%). Kesuksesan ini menegaskan bahwa intervensi ini layak direplikasi, menawarkan solusi yang terukur untuk meminimalisasi limbah padat di sektor pertanian sambil meningkatkan kapasitas, keberlanjutan ekonomi masyarakat lokal, dan membuktikan adopsi teknologi yang mandiri.